Plantas medicinais da caatinga do Nordeste brasileiro: etnofarmacopeia do Professor Francisco José De Abreu Matos - Magalhães, Karla do Nascimento (2019)
Brazil is not only rich in biodiversity, but also in cultural plurality. In the Caatinga (semiarid), an exclusively Brazilian biome , the use of medicinal plants as a therapeutic practice is common among its inhabitants. This biome is also the country's least known, protected and researched ecosystem. The main objective of this work was to construct the Ethnopharmacopoeia of Professor Francisco José de Abreu Matos from the reports of his ethnobotanical expeditions through the Caatinga of the Brazilian Northeast in the period of 1980 1990. As part of the specific objectives, quantitative ethnobotanical techniques were applied: Relative I mportance (RI), Informant Consensus Factor (ICF), Cluster Analysis of Botanical Components (CABC) and Statistical Tests to evaluate the association between categories of use according to the International Classification (ICPC 2/2009) and phylogenetic clade s of angiosperms according to Angiosperm Phylogeny Group (APG IV / 2016). For the confirmation of the species and revision of the botanical nomenclature, consultations were made to the online databases https://www.splink.org, florabrasiljbrj.gov.br, http:/http://www.tropicos.org, www.gbif.org and www.theplantlist.org in addition to visits to the Prisco Bezerra / UFC Herbarium. The botanical confirmation of 272 species and retrieval of 1391 plants’ voucher specimens were possible. Eighty four species 84 (30.9%) had their botanical nomenclature modified. The 272 plants were represented by 71 families, 220 genera and were cited 1,957 times in the travel reports. One hundred and fifty three (56.3%) of these species of plants are native to Brazil. A high number of th ese plants were cultivated (58 species). Of these 153 native species, 36 (23.4%) are endemic to the Caatinga biome. The therapeutic indications attributed to these plants were categorized into 16 body systems according to ICPC 2/2009, which in decreasing o rder of use (RH) were: respiratory system (93 species, 407 UR, ICF 0.77), digestive tract (119 species, 373 RU, ICF 0.68), general and non specific signs/symptoms (95 species, 219 UR, ICF 0.58), female genital tract (60 species, 184 UR, ICF 0.68), skin (71 species, 156 UR, ICF 0.55), circulatory system (50 species, 99 UR, ICF 0.50), blood, hematopoietic and lymphatic organs (46 species, 96 RU, ICF 0.53), urinary tract (44 species, 88 UR, ICF 0.51), musculoskeletal system (33 species, 80 UR, ICF 0.60), psych ological (21 species, 71 UR, ICF 0.60), while others represent less than 10.0% of the UR. The level of underutilization and overuse of certain clades and species is highlighted by cluster analysis. The following parameters were analyzed: RI, ICF and number of citations. We propose selection of plant species with bioprospecting potential: Scoparia dulcis, Egletes viscosa, Libidibia ferrea, Hymenaea courbaril, Ageratum conyzoides, Operculina macrocarpa, Ambrosia artemisiifolia, Cuphea carthagenensis, Combretu m Leprosum, Anacardium occidentale, Myracrodruon urundeuva, Cayaponia tayuya, Solanum paludosum, Anadenanthera colubrina, Amburana cearensis, Pombalia calceolaria, Tarenaya spinosa, Himatanthus drasticus, Senna alata, Lippia alba, Phyllanthus niruri, Arist olochia labiata, Erythroxylum vacciniifolium, Sambucus racemosa, Dysphania ambrosioides, Allium sativum, Pimpinela anisum, Blainvillea acmella, Ambrosia artemisiifolia, Handroanthus impetiginosus, Combretum leprosum and Luffa operculata. The population of the Caatinga biome of northeastern Brazil uses medicinal plants in self care, particularly in the treatment of respiratory diseases, general / nonspecific signs and symptoms, digestive and female genital diseases. The Ethnopharmacopoeia of Professor FJA Ma tos has incalculable cultural, scientific and ecological values, revealing important ethnocultural medicinal plants that deserve special attention, being an important bioprospecting tool and strengthening phytotherapy with Caatinga plant species.